Wnt2bb Induces Cardiomyocyte Proliferation in Zebrafish Hearts via the jnk1/c-jun/creb1 Pathway - Peng, Xiangwen; Fan, Shunyang; Tan, Jing; Zeng, Zhi; Su, Meiling; Zhang, Yuan; Yang, Ming; Xia, Luoxing; Fan, Xuejiao; Cai, Weibin; Tang, Wai Ho (Frontiers in Cell and Developmental Biology, 2020)
Previous studies have demonstrated that inhibition of canonical Wnt signaling promotes zebrafish heart regeneration and that treatment of injured heart tissue with the Wnt activator 6-bromo-indirubin-3-oxime (BIO) can impede cardiomyocyte proliferation. However, the mechanism by which Wnt signaling regulates downstream gene expression following heart injury remains unknown. In this study, we have demonstrated that inhibition of injury-induced myocardial wnt2bb and jnk1/creb1/c-jun signaling impedes heart repair following apex resection. The expression of jnk1, creb1, and c-jun were inhibited in wnt2bb dominant negative (dn) mutant hearts and elevated in wnt2bb-overexpresssing hearts following ventricular amputation. The overexpression of creb1 sufficiently rescued the dn-wnt2bb-induced phenotype of reduced nkx2.5 expression and attenuated heart regeneration. In addition, wnt2bb/jnk1/c-jun/creb1 signaling was increased in Tg(hsp70l:dkk1) transgenic fish, whereas it was inhibited in Tg(hsp70l:wnt8) transgenic fish, indicating that canonical Wnt and non-canonical Wnt antagonize each other to regulate heart regeneration. Overall, the results of our study demonstrate that the wnt2bb-mediated jnk1/c-jun/creb1 non-canonical Wnt pathway regulates cardiomyocyte proliferation.